Health benefits of intentional weight loss - Pi-Sunyer, Xavier (Henry Stewart Talks, 2009)
Medical complications of obesity, Obesity is the primary risk factor for diabetes, Age-adjusted prevalence of hypertension vs. BMI, Metabolic syndrome: clinical identification, Obesity and coronary heart disease mortality, Data supporting life-style intervention, Weight loss and cardiovascular risk, US diabetes prevention program, Study interventions, DPP: lifestyle intervention, Dietary factors that affect energy intake, Weight-Reducing diet, recommended nutrients, Mean change in blood pressure, Mean change in lipids, Thrombogenic and inflammatory risk, Mean change in TPA, Mean change in fibrinogen, Mean change in CRP, Finnish diabetes prevention study, Hazard rate for diabetes and the change in weight, LookAHEAD trial, Trials of hypertension prevention, phase II, Effects of population-based BP reduction, Effect of modest weight loss on cholesterol, Adipose tissue as endocrine cells, Obesity as a therapeutic target for prevention, Cancer incidence attributable to obesity